Inequality across districts and cities in the Riau - Muhammad Hidayat (Universitas Islam Indonesia, 2014)
This research aims to analyze the level of development inequality across regions in the Riau province. This research attempts to identify and analyze the factors that cause inequality as well as to formulate a development policy for reducing inequalities in that region. This study used Theil index and regression analysis. The results of analysis using the Theil index indicate the existence of inequality between different development regions in the Riau Province with the percentage 50%-70%. From the regression analysis, this paper found that some economic and social factors were the important factors of development inequality in the province such as human development index and infrastructure budgets.